Incidence, varietal preference and control of fruit borer, Conopomorpha cramerella ( Lepidoptera: Gracillariidae) on litchi (Litchi chinensis) in Himachal Pradesh - BHATIA, RANJEET; SHARMA, RAVINDER; AGNIHOTRI, R P (The Indian Journal of Agricultural Sciences, 2013)
In a two year study conducted during 1996 and 1997 on the occurrence of litchi fruit borer, Conopomorpha cramerellaSnell. in 8 different blocks of district Kangra, it was observed that pest attack varied between 13.6 and 64.9%. Incidence of the borer on 9 cultivars indicated maximum attack on 'Mclean' (85.7%) while 'Seedless Early' had minimum incidence(33.3%) of the pest. The information on the borer control using 6 different insecticides revealed that the highestefficacy was obtained by using monacrotophos (@0.036% and 0.072%) and cypermethrin (@0.01 and 0.02%) during both the years. The benefit: cost analysis indicated that delayed single spray (15 days before harvest) with endosulphan 0.05%, monocrotophos 0.036%, methyl parathion 0.05% and cypermethrin 0.01% resulted in high returns with a ratio of 1 :35.9, 1 :35.7, 1 :35.1 and 1 :33.5 respectively. Methyl demeton proved to be the least effective insecticide.